Currarino′s triad: Intraoperative ultrasound image-guided surgery - Thambidorai C; Adbel Latif; Zulfiqar A (Wolters Kluwer Medknow Publications, 2010)
This is a report on the use of transperineal intraoperative ultrasound imaging in a case of Currarino′s triad for the first time in the literature.